Ultraviolet photoluminescence in Gd-doped silica and phosphosilicate fibers - Wang, Yun; He, Jing; Barua, Pranabesh; Chiodini, Nortberto; Steigenberger, Sebastian; Abdul Khudus, Muhammad Imran Mustafa; Sahu, Jayanta Kumar; Beresna, Martynas; Brambilla, Gilberto (AIP Publishing, 2017)
Optical fiber lasers operating in the near infrared and visible spectral regions have relied on the spectroscopic properties of rare earth ions such as Yb3+, Er3+, Tm3+, Nd3+, and Sm3+. Here, we investigate Gd3+ doping in phosphosilicate and pure silica fibers using solution doping and sol-gel techniques, respectively, for potential applications in the ultraviolet. Photoluminescence spectra for optical fiber bundles and fiber preforms were recorded and compared. Emissions at 312 nm (phosphosilicate) and 314 nm (pure silica) were observed when pumping to the Gd3+ 6DJ, 6IJ, and 6PJ = 5/2, 3/2 energy levels. Oxygen deficient center was observed in solution doping sample with a wide absorption band centered at around 248 nm not affecting pumping to 6IJ states.